2011
DOI: 10.3109/10903127.2011.561412
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Ambulance Hospital Turnaround Times and Patient Acuity, Destination Hospital, and Time of Day

Abstract: This study demonstrated that patient acuity, destination hospital, and time of day were associated with variation in ambulance turnaround times. Research describing other system characteristics such as current emergency department census and patient handoff procedures may further demonstrate areas for improvement in HTAT. Results from this analysis may be used to inspire EMS administrators and EMS medical directors to start tracking these times to create a predictive model of EMS staffing needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…, Sinnema ) and elsewhere (Vandeventer et al. ). Some hospitals and health authorities have responded with protocols for expediting patients when emergency department congestion reaches certain thresholds (Alberta Health Services ) and such protocols might explain the irregular pattern for average hospital time when the number of busy ambulances is large.…”
Section: Ems System With Repositioningmentioning
confidence: 99%
“…, Sinnema ) and elsewhere (Vandeventer et al. ). Some hospitals and health authorities have responded with protocols for expediting patients when emergency department congestion reaches certain thresholds (Alberta Health Services ) and such protocols might explain the irregular pattern for average hospital time when the number of busy ambulances is large.…”
Section: Ems System With Repositioningmentioning
confidence: 99%
“…Actual historical data on patient arrival rate and traffic was obtained from the South Korean Open Data Portal (data.go.kr) and the Seoul Traffic Information Center, respectively. These data reveal an average of 127.9 calls per day, of which 24.8% are assumed to be high risk [32] The area contains three hospitals with emergency rooms, six ambulances, and six fire stations that function as waiting locations (Figure 5). Actual data on the time-varying demand and changes in ambulance speed over time were also used in the model.…”
Section: Numerical Experiments and Resultsmentioning
confidence: 99%
“…Moreover, the ratio of actual high-risk patients to all patients (Pr H A ) is assumed to be known from the historical data. In this study, Pr H A = 24.8%, according to a survey by Vandeventer et al [32]. Therefore, if α , ÎČ , and Pr H A are known, we can calculate the probability of a patient being correctly classified as high risk (Pr H A |H C ) and vice versa (Pr L A |L C ):PrHAHC=1−αPrHA1−αPrHA+ÎČ1−PrHA,PrLALC=1−ÎČ1−PrHAα·PrHA+1−ÎČ1−PrHA.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Previous investigations have identified that day of the week, time of day, and location are associated with utilization of emergency services (14). Additional information on factors impacting EMS demand could inform EMS administrators in ways to better optimize staffing levels to meet the peaks and troughs of EMS demand (15).…”
Section: Introductionmentioning
confidence: 99%